The Study of Surfaces' Micro- and Nanostructure on Interlayer Cleavages of InSe Layered Crystals Intercalated by Nickel - P.V. Galiy; P. Mazur; A. Ciszewski; I.R Yarovets'; T.M. Nenchuk; Frank Simon; Ya.M. Buzhuk; V.L. Fomenko (Журнал нано- та електронної фізики)
This paper presents the results of experimental study concerning element-phase composition, crystallographic structure, topography and electron-energy structure of interlayer cleavage (0001) surfaces, obtained for nickel intercalated (Ni3dInSe intercalate) InSe layered crystals, by means of qualitative and quantitative X-ray photoelectron spectroscopy (XPS), low energy electron diffraction (LEED) and scanning tunneling microscopy/spectroscopy (STM/STS). It was established that for all layered crystals' intercalates with different concentrations of nickel in initial synthesized InSe + x at.% Ni (x ≤ 10,0 %) alloys and layered crystals further grown from them by Bridgman-Stockbarger method and subjected to intercalation, the maximum concentration of nickel on the cleavage (0001) surfaces of NiхInSe intercalates and, accordingly, in the interlayer gaps of up to 7.67 at. % is observed at 0.75 at. % of nickel in synthesized alloys. Nickel doesn't interact with selenium and indium and there are also no interaction with oxygen and carbon. It is established that nickel is placed in the interlayer gaps of NiхInSe intercalates and, accordingly, appears on the interlayer cleavage (0001) surfaces as fine-phase metal nickel clusters. The studied NiхInSe intercalate system is the perfect hybrid structure with the ability to use in magnetoelectronics.